Information Literacy Skills of Students in Pesantren Environments: A SCONUL Seven Pillars Analysis in Language Learning Contexts - Muhamad Abdul Muid (Literaturia: Journal of Linguistics, Literature, and Language Teaching, 2026)
The digital era demands complex information navigation skills, creating a paradox for pesantren students who possess classical literature mastery but face limited digital access. This study aims to analyze the information literacy skills of these students in composing language-based academic writing using the SCONUL Seven Pillars framework. This qualitative case study involved final-year students at Universitas Islam Internasional Darullughah Wadda’wah. Data were collected through in-depth interviews, observation, and documentation, followed by analysis using the Miles and Huberman interactive model. The results highlight the students' proficiency in identifying, scoping, and critically evaluating printed Arabic literature. Nevertheless, technical gaps in digital literacy remain evident, including minimal application of advanced search strategies (Boolean operators), vulnerability in assessing online source credibility, and a lack of reference management software mastery. The robustness of their print literacy is not yet balanced by adequate digital competencies, hindering the management and presentation stages of international-standard academic writing. These findings contribute a strategic foundation for pesantren library institutions to integrate digital search literacy and citation software training to enhance the quality of students' academic discourse production.